Pengembangan Multimedia Interaktif pada Pembelajaran Menulis Cerita Rakyat Berbasis Literasi Siswa Kelas X SMA Swasta Al-Hidayah Medan - Ayuwaningsih, Windy; Rita, Rita; Safina, Nila (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2024)
This study aims to: (1) Describe the development of interactive multimedia for teaching folklore (saga) writing based on literacy for Class X students at SMA Al-Hidayah Medan. (2) Assess the feasibility of the developed interactive multimedia for teaching folklore (saga) writing based on literacy for Class X students at SMA Al-Hidayah Medan. (3) Evaluate the effectiveness of the interactive multimedia product for teaching folklore (saga) writing based on literacy for Class X students at SMA Al-Hidayah Medan. The research follows the DDD-E model (Decide, Design, Develop, and Evaluate). The participants include content experts, media design experts, graphic design experts, Indonesian language teachers, and Class X students at SMA Al-Hidayah Medan. Validation results from content experts indicate very good criteria for content feasibility (81.2%), presentation feasibility (90%), language usage (83.3%), and graphic design (87.5%). The overall assessment places the interactive multimedia for teaching folklore (saga) writing based on literacy in the "very good" category. Design expert validation results also show very good criteria for guidance and information (87.5%), operational software (87.5%), and systematics, aesthetics, and media principles (81.1%).